The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.nbd.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 receptor dysfunction is rescued by adenosine A2A receptor antagonism in a model of DYT1 dystonia

Abstract: DYT1 dystonia is an inherited disease linked to mutation in the TOR1A gene encoding for the protein torsinA. Although the mechanism by which this genetic alteration leads to dystonia is unclear, multiple lines of clinical evidence suggest a link between dystonia and a reduced dopamine D2 receptor (D2R) availability. Based on this evidence, herein we carried out a comprehensive analysis of electrophysiological, behavioral and signaling correlates of D2R transmission in transgenic mice with the DYT1 dystonia mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 56 publications
6
76
1
Order By: Relevance
“…However, since there is no direct evidence that such mAChR/D2R heterodimers exist, an alternative possibility could be that interactions occur at the level of the signaling pathways. This interpretation is supported by evidence that there is a dramatic decline in the ability of striatal D2Rs to activate their cognate G i/o proteins in transgenic DYT1 mice (Napolitano et al, 2010). …”
Section: Resultsmentioning
confidence: 84%
“…However, since there is no direct evidence that such mAChR/D2R heterodimers exist, an alternative possibility could be that interactions occur at the level of the signaling pathways. This interpretation is supported by evidence that there is a dramatic decline in the ability of striatal D2Rs to activate their cognate G i/o proteins in transgenic DYT1 mice (Napolitano et al, 2010). …”
Section: Resultsmentioning
confidence: 84%
“…In vitro studies, however, have shown that WT mice have a reduction in the autonomous pace-making tone of SCIs in response to striatal HFS, whereas the tonic firing patterns of SCIs in Dyt1 KI mice remain elevated (i.e., LTD deficit: Dang et al, 2012; Maltese et al, 2009; Yokoi et al, 2015). This finding has been attributed to the disrupted binding affinity of D2 dopamine receptors in the indirect basal ganglia pathway (Balcioglu et al, 2007; Calabresi et al, 1992) and the resultant disinhibition of ACh release from SCIs (Dang et al, 2012; Martella et al, 2009; Napolitano et al, 2010; Pisani et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Pettit et al, 1990; Szumlinski et al, 2009). Indeed, abnormalities of dopamine D2 receptors have been identified in DYT1 patients (Carbon et al, 2009) and mice (Napolitano et al, 2010)…”
Section: Discussionmentioning
confidence: 99%